Reassessing Fairness in Digital Financial Services: A Legal Analysis of The FTX Collapse and Global Consumer Protection Standards - Agus Wardhono (Indonesian Journal Publisher, 2025)
This study analyzes fairness as a normative legal principle in digital financial services, particularly within AI- and blockchain-based ecosystems. Using a normative juridical approach, it examines information asymmetry and its impact on consumer protection. The findings show that digital finance, while enhancing efficiency and inclusion, intensifies asymmetry due to algorithmic complexity, opaque governance, and cross-border operations, weakening consumer protection. The FTX collapse illustrates systemic failures in transparency, accountability, and fair treatment, including misuse of funds and inadequate disclosure, violating principles of informed consent and justice. The study argues that technological advancement does not reduce legal responsibility but demands stronger regulatory frameworks. Normatively, fairness is positioned as an enforceable legal standard integrating transparency, accountability, and consumer protection.